PHENOLIC PROFILE, ANTIOXIDANT CAPACITY AND SULFORAPHANE CONTENT DURING THE STORAGE OF BROCCOLI SPROUTS - OLGA NYDIA CAMPAS-BAYPOLI,; ELIZABETH GONZÁLEZ-PACHECO,; ERNESTO URIEL CANTÚ- SOTO,; NORMA PATRICIA SILVA-BELTRÁN,; JOSÉ ANTONIO RIVERA-JACOBO,; MARITZA ARELLANO-GIL, (International Journal of Pharma and Bio Sciences, 2015)
The aim of this investigation was to determine the phenolic profile, antioxidant capacity and sulforaphane content in 3-day-old sprouts during storage at 5°C for 14 days. The content of total polyphenols and antioxidant capacity were determined by spectrophotometric methods; while that phenolic compounds and sulforaphane were quantified by HPLC-DAD. The polyphenol content were present in a range of 6.48 to 13.07 mg GAE/g fresh weight. The DPPH radical scavenging capacity occurred in a range of 21.78 to 29.10 Mmol TE/g fresh weight. Chlorogenic and caffeic acid were found in larger concentration. Sulforaphane content in the sprouts stored at 5ºC showed a reduction of 47% at day 14. The bioactive compounds content in broccoli sprouts may vary in accordance with the time and storage conditions. Broccoli sprouts are an important source of phenolic compounds and sulforaphane.